Effect of transportation on the sympatho-adrenal system responses in horses. (August 2019) - Medica, Pietro; Bruschetta, Giuseppe; Cravana, Cristina; Ferlazzo, Adriana; Fazio, Esterina
Abstract: The objective of current study was to evaluate the effect of transportation stress on the circulating adrenaline (A), noradrenaline (NA) and dopamine (DA) responses of stallions, according to the different distances. Forty-two stallions were studied before and after road transportation of 100, 200 and 300 km, for a period of 1–3 h. An increase in plasma A after 100 km (P < 0.001) was observed. A similar result was seen in plasma NA after 100 km (P < 0.001), and 300 km (P < 0.001). Increases in plasma DA after 100 and 200 km (P < 0.0001) were observed, with a decrease after 300 km (P < 0.0001). Significant interactions among groups and times for A (P < 0.0001), NA (P < 0.0006) and DA (P < 0.0001) changes were observed. These results indicate that the sympatho-adrenal system response of horses was greater after short (100 km), than medium-longer period of transportation (200 and 300 km). This may indicate an adaptation process during transport, considering A and NA as the primary candidate neurotransmitters for the maintenance of homeostatic process to alleviate the effects of the perceived transportation stress. Highlights: Sympatho-adrenal system responses in horses after short transportation were investigated. An increase in circulating adrenaline after transportation of 100 km was observed. Increases in noradrenaline after transportation of 100 km and 300 km were observed. Increases in dopamine after transportation of 100 km and 200 km were observed. Sympatho-adrenal system response was efficiently stimulated by short transportation.